PENGARUH PENJUALAN SECARA ONLINE TERHADAP KEPUTUSAN PEMBELIAN - Ulifa, Mariya; Mulyati, Awin; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2017)
In tody’s era cnsomers prefer to shop online. From that the outhor wants to know the couse of consumers prefer online shopping from offline. To find out online sales of purchasing decisions. In this study is expected to be useful for the development and progress of enter preneur studies especially with regard to online. Add insight for writers and readrs. This research was aiimed to analyze the influence of trust variable, shopping orientation, and service quality, purchase decision in online fashion. This research was a causal comparative research the sample of this research were 100 respondent from 17 Agustus 1945 University student who ever buy online clothe. The teachnique used in this research was simple random sampling. The student showed that partially independent Trust variable (X1), Shopping Orientation variable (X2), Service Quality variable (X3). Dependent, Purchase Decision (Y). Keyword : trust variable, shoppingg orientatio variable, service quality variable, purchase decision.